Effect of Substrate-to-Inoculum Ratio and Temperatures During the Start-up of Anaerobic Digestion of Fish Waste - Yulisa, Arma; Chairattanawat, Chayanee; Park, Sang Hyeok; Jannat, Md Abu Hanifa; Hwang, Seokhwan (Industrial and Domestic Waste Management, 2022)
The high protein and lipid content of fish waste makes mono-digestion a difficult bioprocess for an anaerobic digestion (AD) system. On the other hand, the massive increase in fish and seafood consumption worldwide has led to an inevitable fish waste mono-AD. Therefore, this study was conducted to investigate the effects of food-to-microorganisms (F/M) ratios and temperatures during the start-up period of fish waste mono-digestion. F/M ratios of 0.5, 1, 2, and 3 on a g-COD/g-VSS basis were operated at 35°C and 45°C, representing mesophilic and hyper-mesophilic conditions, respectively. The increase in F/M ratio improved the maximum methane (CH4) production rate at both temperatures. However, F/M ratio of 0.5 generated the highest CH4 yield in mesophilic and hyper-mesophilic conditions (0.23±0.00 L-CH4/g-CODinput). Further increase in F/M ratio decreased CH4 yield up to 21.74% and 39.13% when the reactors were operated at 35°C and 45°C, respectively. When reactors were supplied with FM ratios of 0.5, 1, and 2, hyper-mesophilic temperature improved methanogenesis by up to 2.61% and shortened the lag phase by 22.88%. Meanwhile, F/M ratio 3 at 45°C decreased cumulative CH4 production by up to 26.57% and prolonged the lag phase by 10.19%. The result of this study is beneficial to managing the input substrate of a batch-AD system that treats fish waste as a sole substrate.